2013
DOI: 10.1038/pr.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Association of high levels of α-defensins and S100A proteins with Candida mannan detection in bronchoalveolar lavage fluid of preterm neonates

Abstract: Background: Candida mannan (Mn) detection in bronchoalveolar lavage fluid (BALF) was shown to be useful for earlier identification and preemptive therapy targeting in preterm infants at high risk of invasive Candida infection. We investigated whether early detection of Candida Mn in BALF is associated with the presence of some neutrophilic products, as markers of prenatal infection/inflammation. Methods: BALF specimens were collected during the first 48 h of life from mechanically ventilated preterm newborns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…For HNP-1 through −3 comprise 97% of the total PMN pool, plasma HNPs 1–3 were measured as alarmin of onset of lung injury after cardiac surgery in our study. Previous studies provided supportive evidence that HNPs 1–3, increasing quickly in plasma and BALF [ 20 , 22 , 30 ], initiate the early events in the pathogenesis of acute lung injury in inflammatory lung disease [ 19 , 22 , 24 , 25 ]. High levels of HNPs 1–3 suggested more severe lung injury [ 18 , 20 22 , 24 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For HNP-1 through −3 comprise 97% of the total PMN pool, plasma HNPs 1–3 were measured as alarmin of onset of lung injury after cardiac surgery in our study. Previous studies provided supportive evidence that HNPs 1–3, increasing quickly in plasma and BALF [ 20 , 22 , 30 ], initiate the early events in the pathogenesis of acute lung injury in inflammatory lung disease [ 19 , 22 , 24 , 25 ]. High levels of HNPs 1–3 suggested more severe lung injury [ 18 , 20 22 , 24 ].…”
Section: Discussionmentioning
confidence: 86%
“…Intriguingly, in ARDS patients, the first twelve-hour plasma HNPs levels were found to closely correlate with the release of CRP, IL-8 and G-CSF in the circulation and with the severity of lung injury [ 20 ]. Otherwise, in vitro, stimulation of primary small airway epithelial cells with HNPs 1–3 induced expression of pro-inflammatory cytokines (IL-6, IL-8, IL-1β, IL-13, MCP-1 and 100A proteins), adhesion molecules (ICAM and VCAM), MMP-9 and β-defensins-2, but significantly decreased the expression of anti-inflammatory cytokine IL-10 [ 17 , 22 , 24 , 26 , 30 , 31 ]. These cytokines were always reported to aggravate the HNPs 1–3 induced lung cell damage, lung (microvascular and epithelial) permeability and further diapedesis [ 1 , 2 , 4 , 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…(43)]. Levels of α-defensin have been correlated with the presence of mannan in bronchoalveolar lavage fluids from preterm neonates, indicating a role in controlling fungal growth at mucosal surfaces (44). Complement proteins are another major component, consisting of at least 20 interdependent components that are deposited on the surface of pathogens, resulting in phagocytosis via opsonization, killing via pore-formation, and activation of inflammatory cytokine responses.…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…In addition, Giovanni found that the expression level of S100A8 was correlated with the levels of neutrophils and IL-6 in bronchoalveolar lavage fluid of Candidainfected preterm children, and S100A8 induction was a response to defend against fungal infection by recruiting neutrophils. 29 Under 24 hours treatment with C albicans, the majority of hOMECs died in the present study. Further, the stimulation of S100A8 by C albicans was time-dependent and dose-dependent.…”
Section: (A) (B)mentioning
confidence: 48%